ENHANCING EMPLOYEE PERFORMANCE IN THE CONSTRUCTION AND DESIGN INDUSTRY: A STRATEGIC APPROACH USING THE HR SCORECARD, AHP, AND OMAX - Oemar, Hirawati; Orgianus, Yan; Nurfaza, Aprilia (Center for Study and Journal Management FTI UMI, 2024)
This study addresses PT.X.'s productivity issues in commercial building construction and interior design by developing a precise employee performance measurement system. The motivation arises from the shortcomings of the current evaluation system, which relies heavily on attendance and subjective HR Manager ratings, leading to project delays, customer dissatisfaction, absenteeism, and tardiness. The research proposes a new performance evaluation system by integrating the Human Resources Scorecard, Analytical Hierarchy Process (AHP), and Objective Matrix (OMAX). This approach ensures a comprehensive evaluation by aligning HR practices with the firm's strategic goals. AHP helps prioritize performance indicators objectively, while OMAX sets achievable targets for them. The study identifies 14 strategic objectives and 15 key performance indicators (KPIs) to improve financial performance, internal processes, customer satisfaction, and learning and growth metrics. The analysis reveals that 7 out of the 15 KPIs perform poorly, indicating the need for targeted improvements. Key recommendations include enhancing project management, implementing compliance regulations and penalties, introducing performance bonuses, and investing in staff training. The study provides actionable insights for managers and HR professionals seeking to implement quantitative and objective performance measurement systems. The findings can guide PT.X. and similar organizations in aligning their strategic goals with HR practices and enhancing overall productivity. The research is innovative in applying the HR Scorecard, AHP, and OMAX within the construction and design industry. This objective and systematic approach offers a significant opportunity for organizational growth by enhancing the measurement and improvement of employee performance.